Research Progress of Silicon Suboxide-Based Anodes for Lithium-Ion Batteries - Zhou, Xiaozhong; Qi, Zhaoyi; Liu, Qiang; Tian, Jibin; Liu, Mingxia; Dong, Kaifa; Lei, Ziqiang (Frontiers in Materials, 2021)
With unique advantages, such as high energy density, long lifespan and environmental friendliness, lithium-ion batteries (LIBs) have been widely used in various portable electronics, and placed great expectations on the application in electric vehicles. To meet the ever-increasing high-energy-density demand of the next-generation LIBs, silicon suboxide SiOx(0